The Role of Hydrophobicity and Surface Receptors at Hyphae of Lyophyllum sp. Strain Karsten in the Interaction with Burkholderia terrae BS001 – Implications for Interactions in Soil - Vila, Taissa; Nazir, Rashid; Rozental, Sonia; dos Santos, Giulia M. P.; Calixto, Renata O. R.; Barreto-Bergter, Eliana; Wick, Lukas Y.; van Elsas, Jan Dirk (Frontiers in Microbiology, 2016)
The soil bacterium Burkholderia terrae strain BS001 can interact with varying soil fungi, using mechanisms that range from the utilization of carbon/energy sources such as glycerol to the ability to reach novel territories in soil via co-migration with growing fungal mycelia. Here, we investigate the intrinsic properties of the B. terrae BS001 interaction with the basidiomycetous soil fungus Lyophyllum sp. strain Karsten. In some experiments, the ascomycetous Trichoderma asperellum 302 was also used. The hyphae of Lyophyllum sp. strain Karsten were largely hydrophilic on water-containing media versus hydrophobic when aerial, as evidenced by contact angle analyses (CA). Co-migration of B. terrae strain BS001 cells with the hyphae of the two fungi occurred preferentially along the - presumably hydrophilic - soil-dwelling hyphae, whereas aerial hyphae did not allow efficient migration, due to reduced thickness of their surrounding mucous films. Moreover, the cell numbers over the length of the hyphae in soil showed an uneven distribution, i.e. the CFU numbers increased from minima at the inoculation point to maximal numbers in the middle of the extended hyphae, then decreasing towards the terminal side. Microscopic analyses of the strain BS001 associations with the Lyophyllum sp. strain Karsten hyphae in the microcosms confirmed the presence of B. terrae BS001 cells on the mucous matter that was present at the hyphal surfaces of the fungi used. Cell agglomerates were found to accumulate at defined sites on the hyphal surfaces, which were coined ‘fungal-interactive’ hot spots. Evidence was further obtained for the contention that receptors for a physical bacterium-fungus interaction occur at the Lyophyllum sp. strain Karsten hyphal surface, in which the specific glycosphingolipid ceramide mono hexoside (CMH) plays an important role. Thus, bacterial adherence may be mediated by heterogeneously-distributed fungal-specific receptors, implying the CMH moieties. This study sheds light on the physical aspects of the B. terrae BS001 – L. sp strain Karsten interaction, highlighting heterogeneity along the hyphae with respect to hydrophobicity and the presence of potential anchoring sites.